(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMAIRE: 1 - Introduction - 2. L’État et l’Église en Grèce. Le cadre constitutionnel - 3 - L’Église de Grèce comme institution de l’État grec - 4. Le discours constitutionnel de l’Église. Des éléments de constitutionnalisme populiste - Pluralisme constitutionnel et droits de la majorité - 6. Les droits en tant qu’identité - 7. Conclusion - Bibliographie. ABSTRACT: The invocation of the people, the constitution and the rights occupies an important place in the public discourse of the Church of Greece. Its constitutional discourse exhibits two main characteristics. Firstly, it is a populist discourse. The church talks in the name of “its” people, which it identifies with the Greek nation, and as the voice of the people’s will against its rulers. Moreover, it is a rights-laden discourse. The church talks as the protector of the rights of the majority, which it identifies with the rights of its believers. Its constitutional discourse and practice shows that the church manages to exploit the institutions, achievements and discourses of modernity, if only for the promotion of apparently pre-modern ends: the preservation of its privileges against the other religions; the prolongation of its role in the public sphere; its reproduction as an ideological mechanism of the nation-state.